2015
DOI: 10.7326/m14-2957
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Proprotein Convertase Subtilisin/Kexin Type 9 Antibodies in Adults With Hypercholesterolemia

Abstract: CRC 1116 Masterswitches in Myocardial Ischemia, German Research Council DFG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
271
1
17

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 385 publications
(297 citation statements)
references
References 35 publications
8
271
1
17
Order By: Relevance
“…No statistically significant differences were identified in study‐level subgroup analyses including patients on or off treatment with a background statin and patients with FH. In contrast with a previous meta‐analysis from lipid‐lowering trials,47 we found no benefit in all‐cause mortality with PCSK9 inhibitor therapy. This finding may be attributable to the fact that our analysis included 2 large trials of populations with a baseline LDL‐C of <100 mg/dL,5, 20 contributing to an overall baseline LDL‐C of 106 mg/dL in our pooled sample.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…No statistically significant differences were identified in study‐level subgroup analyses including patients on or off treatment with a background statin and patients with FH. In contrast with a previous meta‐analysis from lipid‐lowering trials,47 we found no benefit in all‐cause mortality with PCSK9 inhibitor therapy. This finding may be attributable to the fact that our analysis included 2 large trials of populations with a baseline LDL‐C of <100 mg/dL,5, 20 contributing to an overall baseline LDL‐C of 106 mg/dL in our pooled sample.…”
Section: Discussioncontrasting
confidence: 99%
“…Until recently, the highest quality of evidence surrounding alirocumab and evolocumab stemmed from phase 2 and 3 lipid‐lowering trials and their meta‐analyses 46, 47. The encouraging results led to the 2015 US Food and Drug Administration fast‐track approval for use of PCSK9 inhibitors as adjuncts to diet and maximally tolerated statin for patients with FH and clinical ASCVD.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, no treatment option has been established for high Lp(a) levels, other than experimental and observational regimes 27, 28, 29, 30, 31, 32, 33. Moreover, to date, no randomized controlled trials have directly evaluated the effect of lowering Lp(a) on cardiovascular outcomes including AS development.…”
Section: Discussionmentioning
confidence: 99%
“…Los efectos adversos importantes no aumentaron con la administración de anticuerpos PCSK9, considerándose seguros y efectivos para los adultos con dislipidemia. La importante limitación de este metaanálisis es que los estudios que incluye no estaban diseñados para ver eventos y hay que esperar el desarrollo de nuevos estudios que están en desarrollo 10 .…”
Section: Anticuerpos Humanos Monoclonales Anti-pcsk9unclassified